2021
DOI: 10.1136/postgradmedj-2021-140564
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and mortality with SARS-COV-2 infection: a retrospective two-centre cohort study

Abstract: BackgroundThe role of vitamin D in increased mortality with SARS-COV-2 virus, namely, COVID-19, remains uncertain. We analysed all the patients who were treated as COVID-19-positive with or without a positive swab and were tested for vitamin D levels.MethodsThis was a retrospective, study involving 1226 patients swabbed for SARS-CoV-2 between the 10 February 2020 and 1 May 2020 at two hospitals of East Sussex Healthcare NHS Trust. Patients who were swab-positive for COVID-19 or treated as COVID-19-positive on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Retrospective cohort studies by Zafar et al have recently published work comparing the outcomes of COVID-19 mortality associated with high HbA1c levels, low Vitamin D levels, and low lymphocyte counts. They have concluded that there are more associations with increased mortality and the cumulative sum of comorbidities rather than absolute blood or serum counts for vitamin D levels and lymphocyte counts [19,20]. These researches point towards more association of comorbidity towards increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective cohort studies by Zafar et al have recently published work comparing the outcomes of COVID-19 mortality associated with high HbA1c levels, low Vitamin D levels, and low lymphocyte counts. They have concluded that there are more associations with increased mortality and the cumulative sum of comorbidities rather than absolute blood or serum counts for vitamin D levels and lymphocyte counts [19,20]. These researches point towards more association of comorbidity towards increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested an association of co-morbidities with the COVID-19 infection [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Alsafar et al [ 11 ] showed that gender and comorbidities did not contribute to the mortality. However, in a retrospective two-center cohort study in UK including 433 COVID-19 patients, non-survivors were significantly older and more likely to have comorbidities [ 21 ]. This goes in line with a Brazilian study that had indicated a statistically significant correlation between mortality and both diabetes mellitus and hypertension [ 12 ].…”
Section: Discussionmentioning
confidence: 99%